Pain Management in Dentistry: Current Strategies and Emerging Technologies - Naif Mohammed Mujahhiz alruqi,; Khulood Nader Felemban,; Arwa Abdulrahman ‏Alhawsawi,; Sahar Husain Abushal,; Asrar Faraj Almoualad,; Jawhara Mousa Zabarmawi,; Maha Mustafa Magleh,; Mohra Nasser Aalzaed,; Nouf Mohammed Alhusami,; Mohammed Ali Alkithri, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Effective pain management is crucial for ensuring patient comfort and compliance in dental care. This study explores contemporary pain management strategies in dentistry while highlighting emerging technologies that offer promising advancements. Utilizing secondary data from a comprehensive review of existing literature, dental journals, and clinical studies, the research identifies current methods such as local anesthesia, analgesics, and sedation techniques. It also delves into the psychological and behavioral approaches employed to alleviate dental anxiety and pain perception. Emerging technologies, including laser dentistry, computer-assisted anesthesia, and regenerative techniques, are examined for their potential to enhance patient outcomes. Laser-assisted procedures, with their reduced need for anesthesia, hold promise for less invasive treatments. Computer-assisted delivery systems offer precision in anesthetic administration, potentially minimizing patient discomfort. Additionally, advancements in regenerative medicine, such as stem cell therapy and tissue engineering, are showing potential for pain reduction in restorative dentistry. This comprehensive analysis underscores the dynamic landscape of dental pain management, advocating for continued research and integration of novel technologies into practice. Clinicians must stay abreast of these developments to optimize patient care. The study concludes that while traditional methods remain foundational, the incorporation of emerging technologies can significantly improve pain management protocols, making dental procedures more tolerable and enhancing overall patient satisfaction.